2007
DOI: 10.1371/journal.pbio.0050035
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Diverse Toxicants Converge on Fyn and c-Cbl to Disrupt Precursor Cell Function

Abstract: Identification of common mechanistic principles that shed light on the action of the many chemically diverse toxicants to which we are exposed is of central importance in understanding how toxicants disrupt normal cellular function and in developing more effective means of protecting against such effects. Of particular importance is identifying mechanisms operative at environmentally relevant toxicant exposure levels. Chemically diverse toxicants exhibit striking convergence, at environmentally relevant exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 176 publications
7
71
1
1
Order By: Relevance
“…methylmercury, lead, paraquat) in the absence of differentiating factors in the medium. 57,58 However, when differentiating factors are added to the medium, a deficit in GSH induced either by GCLC shRNA (this study) or BSO 59 impairs oligodendrocyte maturation. These latter in vitro data are consistent with the impaired oligodendrocyte and myelination observed in GCLM-KO mice.…”
Section: Discussionmentioning
confidence: 76%
“…methylmercury, lead, paraquat) in the absence of differentiating factors in the medium. 57,58 However, when differentiating factors are added to the medium, a deficit in GSH induced either by GCLC shRNA (this study) or BSO 59 impairs oligodendrocyte maturation. These latter in vitro data are consistent with the impaired oligodendrocyte and myelination observed in GCLM-KO mice.…”
Section: Discussionmentioning
confidence: 76%
“…We showed that ephrinA5 colocalized with EGFR in certain regions on the plasma membrane. As phosphorylation by Fyn has been reported to regulate the E3 ligase activity of c-Cbl (Grossmann et al, 2004;Li et al, 2007), we hypothesize that the ephrinA5 reverse signaling triggered by EphA2-Fc would activate Fyn, which could phosphorylate c-Cbl, and facilitate c-Cbl-mediated EGFR degradation.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, we were also intrigued by the up-regulation of the heme oxygenase 1 (Hmox1) transcript in both datasets. Previously, Cbl was shown to be involved in responses to toxicants and oxidative stresses (30)(31)(32). Although we did not observe global up-regulation of oxidative stress-induced genes in the present datasets, because of these previous reports we decided to examine the oxidative stress pathway as well.…”
Section: Mec Survival Is Impaired In the Complete Absence Of Cbl Famimentioning
confidence: 61%